The Role of Bond Covenants and Short-Term Debt: Evidence from Brazil - Vinícius Augusto Brunassi Silva; Richard Saito; Fernando Carvalhaes Barbi (BAR: Brazilian Administration Review, 2013)
This paper examines the role of financial covenants as substitutes for short-term debt and a possible trade off between short-term debt and long-term debt, especially for companies with growth opportunities. Using a sample of 159 corporate bonds issued on the Brazilian Market, we found evidence that: first, financial covenants and short-term debt are substitute tools to minimize agency conflict, as per literature confirming that stronger financial covenants could limit the possible expropriation of debt holders and in exchange debt holders may be willing to lend at longer terms and; second, companies with growth opportunities are willing to exchange shortterm debt for long-term debt under the presence of covenants. Most importantly, this does not seem to be a restriction for financing growth opportunities.